(untitled) (Research, Society and Development, 2021)
The formation of human dentition occurs from the fifth week of intrauterine life, during the formation phases, episodes that interfere with the formation of teeth can occur, causing changes such as numbers. This alteration is known as the supernumerary teeth, being characterized as an increase in the number of teeth, in addition to the normal teeth. They are occasionally impacted by the lack of space to break out. Treatment depends on a detailed clinical and complementary examination, and extraction is often the best option. There are several tests for diagnosis and planning, with computed tomography as the best option, mainly because it offers a three-dimensional image. Our objective was to perform a literature review and a clinical case report on the presence of multiple impacted teeth in a diagnosed patient without syndromes. The literature review included articles in the English language published since 2006. For the case report, information from medical records such as medical history, clinical examination and tomography were used. It was concluded that supernumerary teeth in non-syndromic patients may be related to changes in signaling modulation that control dental development, failure of inhibitors responsible for apoptosis of dental sprouts, in addition to a possible autosomal dominant increase.